Perbedaan Mutu (Karbohidrat, Serat dan Vitamin C) Serta Daya Terima Jus Tomat (Lycopersicum esculentum var. grandifolium) Berkulit Dan Tanpa Kulit yang Diolah Menggunakan Berbagai Alat Pengolahan sebagai Minuman Alternatif Penderita Diabetes Melitus - Nany Suryani; Alfan Bakhtiarsyah; Desy Erianti; STIKES Husada Borneo; RSUD Dr. H. Moch. Ansari Saleh Banjarmasin; Alumni STIKES Husada Borneo, (Jurnal Kesehatan Indonesia, 2016)
Diabetes mellitus is a chronic abnormalities in glucose homeostasis. One of the ingredients of foods associated with diabetes mellitus namely tomato. Tomatoes contain low carbohydrates, sufficient fibers and vitamin C. However, the potential difference in the content of carbohydrates, fiber and vitamin C may occur in the processing of tomato juice with and without skin treated with different processing tool. The purpose of this study was to analyze the content of carbohydrates, fibers and vitamin C as well as the acceptability (colour, smell, texture and taste) on tomato juice with skin and without the skin treated with different processing tool. Data analysis methods are used, namely Two Way Anova and Friedman test. The result showed there is differences in the carbohydrate content and acceptability (color, smell, taste) of tomato juice with and without the skin treated with different processing tools, and there is no differences in the fibers, vitamin C content and acceptability (texture) of tomato juice with and without the skin treated with different processing tool.